Membrane characterization for electrochemical LiOH production from Li2SO4 with simultaneous H2SO4 valorization - Henderson, Guillaume; Martin Diaz, Lara; Schutyser, Wouter; Bonin, Luiza (Frontiers in Membrane Science and Technology, 2024)
This work characterized different cation- and anion-exchange membranes to improve the efficiency for the electrochemical conversion of Li2SO4 into LiOH and simultaneously recover H2SO4 as a byproduct, an essential process for sustainable alternatives for lithium−ion battery recycling. The membrane’s ability to block H+ and OH- migration over the membrane to the feed stream of the electrolyzer was investigated. Simultaneously, the membrane resistance was measured to assess its impact on the cell voltage and overall energy consumption. The best CEM, Sx-2301-Wn, enabled to concentrate LiOH up to 1.7M with a current efficiency (CE) of 77.3%, while Fumasep FAB-130-PK, the best AEM, was able to concentrate H2SO4 up to 0.6M with a CE of 74.6%. The recirculation of LiOH into the middle compartment to maintain a constant pH was also investigated and showed to improve both Li+ (4.2-8%) and SO42- (5.1%) migration, but pH higher than 3 led to an increased membrane resistance. The results of this work contributed to the selection of a suited membrane and ideal operational conditions for producing LiOH and H2SO4 through a three-compartment membrane electrolysis cell.